Pengembangan Bahan Ajar Menulis Puisi Melalui Media Pembelajaran Buku Tiga Dimensi pada Siswa Kelas X SMK Swasta Abdi Negara Binjai - Winastasia, Novia; Rita, Rita; Lubis, Hasrita (Medan Resource Center, 2024)
This study aimed to assess the validity, practicality, and effectiveness of three-dimensional book learning media for writing poetry in class X. Employing the 4D Research and Development model (Define, Design, Development, Disseminate), the quantitative approach and Pre-Experimental Design were utilized for data analysis and media effectiveness testing, respectively. Validation involved four participants: two material experts (90.66%) and two media experts (89%), all categorized as